Errores de tipo en Alemania y en Colombia: comparación de Derecho Penal - Bott, Ingo (2023)
The article begins by presenting the difference between a mistake in typification, which involves the elements of a crimeís typification, and a mistake in law, which occurs with regard to the legal prohibition of a certain act. Based on this distinction, the article then turns to mistakes in typification, showing the effect of excluding the intention to harm while preserving negligence. This section also includes the mistake of privileged typification. Afterward, the authors explain the mistake in the person, and, through a series of examples, they consider possible variants of this kind of mistake. This leads to the study of mistakes in the act, as part of the authorsí goal of analyzing aberratio ictus. When this ìmistakeî becomes associated with the eventual intention to harm, another problem arises, which is also analyzed in the article. After this, the authors examine dolus generalis, which refers to the link of causality, that is, to the way the action that gives rise to the criminal act is developed. Next, the article focuses on aberratio delicti, an event solved according to the rule of the intention to harm. Finally, the authors turn to the agentís mistake in deflecting the development of the path of causality, which leads to the problem of objective imputation. One can conclude that there are similarities between the German and the Colombian criminal law systemsí codification and treatment of mistakes.